2017
DOI: 10.1509/jppm.15.024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Cigarette Addiction Warnings and Health-Related Claims on Consumers’ Risk Beliefs and Use Intentions

Abstract: The popularity of electronic cigarettes continues to skyrocket across the United States. Given the multitude of aggressive promotional campaigns launched by e-cigarette manufacturers, including some that have offered unsubstantiated health claims, this rapid growth is not surprising. Despite this popularity, many consumers may be unaware that some in the health care community consider e-cigarette use a serious public health issue because most e-cigarettes deliver highly addictive nicotine through vapor. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 50 publications
(139 reference statements)
0
39
1
Order By: Relevance
“…Recently, researchers have begun evaluating messages about comparative risks of electronic and combusted cigarettes 17–24. Quantitative studies of comparative risk messages have reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have begun evaluating messages about comparative risks of electronic and combusted cigarettes 17–24. Quantitative studies of comparative risk messages have reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lee et al () found that those exposed to warning labels on an e‐cigarette product found the information easy to understand and prompted them to be concerned about health risks, and half of the participants not exposed to a warning label actually reported having seen one. Furthermore, Berry, Burton, and Howlett () found a significant influence of addiction warning labels on e‐cigarette perceptions across all consumer segments, although the effect was attenuated in the presence of a positive health claim. In combination, prior work illustrates the potentially influential and positive role of warning labels for e‐cigarettes, yet similarly highlights needed areas of inquiry surrounding more expansive health awareness and messaging.…”
Section: Mixed‐messages: Sources Of Information For Consumersmentioning
confidence: 99%
“…Within the e‐cigarette domain, recent scholarship addressing addiction‐specific warning labels illustrates a greater awareness of addiction risk when a warning label is present (Berry, Burton, and Howlett ). We build on this finding to explore how communicating different forms of health‐risk information may influence consumers' understanding and acceptance of risk, comparing across consumer use segments.…”
Section: Study 2: Influence Of Warning Labels On Consumer Risk Percepmentioning
confidence: 99%
“…Because the perception that ENDS are less harmful than cigarettes is usually cited as one of the most important reason for their use [ 8 , 9 ], it is imperative to understand how to communicate to the public about the comparative risk of ENDS and cigarettes. However, only a few studies have examined the effects of messages communicating the risk differential between ENDS and combusted cigarettes [ 10 , 11 , 12 , 13 , 14 , 15 ]. These studies found that comparative risk messages about ENDS were able to reduce smokers’ perceived risk of ENDS relative to combusted cigarettes [ 13 , 14 , 15 ], increase smokers’ interest in using ENDS [ 10 , 16 ], and reduce smoking intentions [ 15 ] and smoking behavior during the study [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While effects of messages on comparative ENDS risks have sometimes been evaluated among separate demographic groups or by product use status [ 10 , 12 , 48 ], past research has not employed more nuanced psychographic segmentation to determine the target audiences. Informed by the aforementioned theoretical models of segmentation and the previous segmentation efforts in the tobacco domain [ 10 , 49 ], we took individual-level characteristics, including current and previous tobacco use behavior practices, cognitions about ENDS use, and demographic information, to be the focal segmentation parameters in the present study.…”
Section: Introductionmentioning
confidence: 99%